Fabricating 3D ordered marcoporous Na2MnSiO4/C with hierarchical pores for fast sodium storage. (10th April 2018) - Zhang, Datong; Ding, Zhengping; Yang, Ying; Zhao, Shuai; Huang, Qun; Chen, Cheng; Chen, Libao; Wei, Weifeng
Abstract: Despite being considered as a promising candidate for cathode of next-generation batteries, sodium manganese orthosilicate suffers from sluggish kinetics, while no effective enhancement through structural manipulation has been reported yet. Herein a three-dimensionally ordered macroporous Na2 MnSiO4 /C is fabricated via a templated sol-gel method and investigated as a cathode material for sodium ion batteries. It delivers a high initial reversible capacity of 207 mAh g −1 (∼1.5 mol of Na + insertion/extraction) at 0.1 C (1C = 139 mAh g −1 ), excellent high-rate capability (76 mAh g −1 at 5 C) and long-term cyclability (76.0% after 345 cycles at 2 C). The superior electrochemical properties are ascribed to short Na-ion diffusion path of honeycomb-like 3D ordered macroporous structure, fast electron transportation of interconnected carbon frameworks and effective constraint of volumetric changes upon electrochemical cycling. The rational design of 3D ordered porous structure may facilitate the development of silicate-based cathode materials that have problems of low electronic conductivity, slow ion diffusion and structural instability for new high-energy sodium ion batteries.